2003
DOI: 10.1161/01.hyp.0000069011.18333.08
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Growth Factor Responses in Vascular Smooth Muscle Cells Derived from 12/15-Lipoxygenase–Deficient Mice

Abstract: Abstract-Biochemical and genetic evidence support the involvement of leukocyte-type 12/15-lipoxygenase enzyme and its products in the atherogenic process. We recently showed that products of the 12/15-lipoxygenase pathway play an important role in mediating hypertrophy, matrix protein production, and inflammatory gene expression in vascular smooth muscle cells (VSMC) through activation of mitogen activated protein kinases and key transcription factors. The current study is aimed at establishing the in vivo rol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
49
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(52 citation statements)
references
References 58 publications
3
49
0
Order By: Relevance
“…Aortic VSMCs from 9-to 10-week-old male db/ϩ and db/db mice (MVSMCs) were isolated by enzymatic digestion as described earlier (34) and cultured in Dulbecco's modified Eagle's (DME)-F12 culture medium supplemented with 10% FCS. MVSMCs from db/ϩ and db/db mice were used between passages 5 and 8.…”
Section: Phosphospecific Antibodies For P38mentioning
confidence: 99%
See 1 more Smart Citation
“…Aortic VSMCs from 9-to 10-week-old male db/ϩ and db/db mice (MVSMCs) were isolated by enzymatic digestion as described earlier (34) and cultured in Dulbecco's modified Eagle's (DME)-F12 culture medium supplemented with 10% FCS. MVSMCs from db/ϩ and db/db mice were used between passages 5 and 8.…”
Section: Phosphospecific Antibodies For P38mentioning
confidence: 99%
“…Oxidant stress. Intracellular superoxide production (index of oxidant stress) was evaluated with the use of a superoxide probe dihydroethidium (Molecular Probes, Eugene, OR) as described earlier (34). Cell migration.…”
Section: Phosphospecific Antibodies For P38mentioning
confidence: 99%
“…With regard to their tissue distribution, while 15-LOX1 shows a narrow cell-specific expression, including human reticulocytes and airway epithelial cells, 15-LOX2 appears to be expressed in epithelial cell types in cornea, lung, prostate, and skin (5). Although the presence of 15-LOX2 in the vessel wall has yet to be reported, vascular smooth muscle cells (VSMC) and endothelial cells (EC) express 15-LOX1 (also known as 12/15-LOX in murines) and when exposed to AA, these cells produce 15(S)-HETE and 12(S)-HETE (6)(7)(8)(9). A number of studies have demonstrated that 15-LOX1 and its murine ortholog 12/15-LOX play a role in atherosclerosis (10)(11)(12).…”
Section: Both Enzymes Metabolize Linoleic Acid (La) To 13(s)-hydropermentioning
confidence: 99%
“…Previously we have shown that 15(S)-HETE stimulates JNK1 in HRMVEC (7). To understand the mechanisms of JNK1 activation by 15(S)-HETE, here we have examined the role of Src and Rac1.…”
Section: (S)-hete Activates Jnk1 In Hrmvec Via Src-rac1 Signalingmentioning
confidence: 99%
“…5,7,8 Compared with VSMCs from C57BL/6 (BL-6) mice, VSMCs from 12/15LO-overexpressing transgenic (12/15LO-tg) mice grow faster, and VSMCs from 12/15LO Ϫ/Ϫ mice grow slower and display decreased S-phase entry in culture. 9,10 12/15LO and its products are increased in the vascular wall of animal models of atherosclerosis and injury-induced restenosis. 11 Compared with uninjured carotids, 12/15LO expression is significantly increased in rat carotids on day 12 after injury.…”
mentioning
confidence: 99%